2022
DOI: 10.6007/ijarbss/v12-i12/15590
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Development Research in Tourism and Hotel: A Review of Current Literature and Suggestions for Future

Abstract: The purpose of this paper is to provide a review of human resource development literature from the points of view of both human resource development and hospitality and tourism. The paper provides a critical, qualitative, and comparative review of HRD research literature on human resource development and hospitality and tourism, providing insights into emerging research trends and pointing to the gaps in the literature. The review result showed six streams of research from the hospitality and tourism literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Hosen et al studied employees in star-rated hotels and found that training, skill enhancement, and career development influenced the organizational commitment, which, in turn, improved the job performance. Organizational commitment served as a mediator between skill-enhancing training and job performance, as well as career development and job performance [28]. Similarly, Chiampou et al found that nurses' participation in continuous training programs positively impacted their organizational commitment, particularly in enhancing professional service, collegial learning and interaction, personal benefits and job security, and personal commitment and reflection.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Hosen et al studied employees in star-rated hotels and found that training, skill enhancement, and career development influenced the organizational commitment, which, in turn, improved the job performance. Organizational commitment served as a mediator between skill-enhancing training and job performance, as well as career development and job performance [28]. Similarly, Chiampou et al found that nurses' participation in continuous training programs positively impacted their organizational commitment, particularly in enhancing professional service, collegial learning and interaction, personal benefits and job security, and personal commitment and reflection.…”
Section: Organizational Commitmentmentioning
confidence: 99%